Self-concept of mathematically gifted and non-gifted high school students: The effect of achievement level - Rovan, Daria (Array, 2003)
The aim of this study was to explore the effect of level of mathematical giftedness and student's gender on students' personal competence perceptions, fear of negative evaluation and self-esteem, controlling for their general school achievement. Participants in the study were high school students forming three groups: highly gifted (N=62), moderately gifted (N=99) and non-gifted students (N=77). The results showed that mathematically gifted students did not differ from their non-gifted peers in their personal competence, fear of negative evaluation and their self-esteem evaluations. The effect of gender was significant only for the fear of negative evaluation indicating that female student show more intensive fear than their male peers do. The most interesting result is the interaction between gender and mathematical giftedness level for the measure of self-esteem.